Unilateral jumps in different directions: a novel assessment of soccer-associated power? - Murtagh, C. F.; Vanrenterghem, J.; O`Boyle, A.; Morgans, R.; Drust, B.; Erskine, R. M. (Journal of Science and Medicine in Sport, 2017)
Objectives: We aimed to determine whether countermovement jumps (CMJs; unilateral and bilateral) performed in different directions assessed independent lower-limb power qualities, and if unilateral CMJs would better differentiate between elite and non-elite soccer players than the bilateral vertical (BV) CMJ. Design: Elite (n = 23; age, 18.1 ± 1.0 years) and non-elite (n = 20; age, 22.3 ± 2.7 years) soccer players performed three BV, unilateral vertical (UV), unilateral horizontal-forward (UH) and unilateral medial (UM) CMJs. Methods:Jump performance (height and projectile range), kinetic and kinematic variables from ground reaction forces, and peak activation levels of the vastus lateralis and biceps femoris (BF) muscles from surface electromyography, were compared between jumps and groups of players. Results: Peak vertical power (V-power) was greater in BV (220.2 ± 30.1 W/kg) compared to UV (144.1 ± 16.2 W/kg), which was greater than UH (86.7 ± 18.3 W/kg) and UM (85.5 ± 13.5 W/kg) (all, p < 0.05) but there was no difference between UH and UM (p = 1.000). Peak BF EMG was greater in UH compared to all other CMJs (p = 0.001). V-power was greater in elite than non-elite for all CMJs (p = 0.032) except for BV (p = 0.197). Elite achieved greater UH projectile range than non-elite (51.6 ± 15.4 vs. 40.4 ± 10.4 cm, p = 0.009). Conclusions: We have shown that UH, UV and UM CMJs assess distinct lower-limb muscular power capabilities in soccer players. Furthermore, as elite players outperformed non-elite players during unilateral but not BV CMJs, unilateral CMJs in different directions should be included in soccer-specific muscular power assessment and talent identification protocols, rather than the BV CMJ.